Accessible Computer Technologies for Students With Disabilities in Canadian Higher Education - Catherine S. Fichten; Jennison V. Asuncion; Chantal Robillard; Myrtis E. Fossey; Maria Barile (The Canadian Network for Innovation in Education (CNIE), 2003)
Two studies explored how well English and French speaking colleges and universities in Canada address availability and access to new computer and information technologies for individuals with disabilities. In Study 1, 156 professionals who provide disability-related supports on campus responded to structured interview questions. In Study 2, 40 professionals who work in Quebec's Francophone junior/community college system (CEGEP) participated. Results showed that most institutions had specialized adaptive computer equipment, though colleges were less likely than universities, and loan programs providing adaptive computer equipment were seen as very effective. Respondents believed they were not very knowledgeable about adaptive computer technologies and those from Francophone institutions scored lower than from Anglophone institutions. The needs of students were seen as moderately well met, with Francophone respondents more favorable than Anglophone. Respondents from Anglophone universities expressed different needs than those from Anglophone colleges or Francophone institutions. Disability service providers wished students were better equipped and prepared for the postsecondary experience, computer based teaching materials used by professors were more accessible, and more extensive support services for adaptive hardware and software available. We provide recommendations based on universal design principles that are targeted at those involved in technology integration in postsecondary education.